Legitimising informal markets: A case study of the dairy sector in Kenya - Blackmore, E.; Alonso, Silvia; Grace, Delia (International Institute for Environment and Development, 2015)
When five per cent of milk fails to meet standards, you have a problem with milk. When 50 per cent does not meet standards, you have a problem with standards. In developing countries, perishable food is mostly sold in informal markets and often does not meet national food safety standards. Government regulation in informal markets has not improved food safety in the past and formalisation does not guarantee safe food. New approaches, based on gradual improvements and an inclusive path to formalisation, show greater promise. A scheme to train and legitimise dairy traders in Kenya has revealed benefits for public health, farmers, vendors and consumers. But governments must withstand pressure from vested interests and show genuine commitment to supporting progressive, effective and inclusive policies if these are to be successful.